Developing clinoptilolite nanoparticle-reinforced agar-g-poly(acrylic acid) hydrogels for plant tissue culture. (26th September 2018) - Khoshbin, Shohreh; Solgi, Mousa; Taghizadeh, Mina; Heidarian, Pejman
Abstract: In this study, agar-g-poly(acrylic acid) hydrogels, reinforced by clinoptilolite nanoparticles, were prepared to be applied in plant tissue culture. For this purpose, different percentages of acrylic acid monomer (0, 25, 50, 75, and 100 wt%) were grafted onto the backbone of agar in order to find the most suitable hydrogel for tissue culture of African violet leaves, a plant commonly considered in regeneration studies. In order to evaluate the resulting nanocomposite hydrogels (as the culture media), the necrosis study of tissue culture-raised African violet leaves was conducted along with their biological properties, including fresh weight, dry weight, length and number of shoots, leaf width, and chlorophyll content index. Furthermore, morphological, mechanical, and physical studies of the resulting hydrogels as well as their in vitro degradations were also carried out to determine the influence of graft polymerization on the properties of agar-g-poly(acrylic acid) hydrogels. The results showed that the graft polymerization of acrylic acid monomer up to 25 wt% would improve the regeneration of African violet leaves on the obtained media. Additionally, those hydrogels with 25 and 50 wt% poly(acrylic acid) among all the specimens proved to be the most suitable samples in terms of water capacity, strength, and porosity. This study also showed that the preparing the media from agar-g-poly(acrylic acid) could be more economic than from the pure agar hydrogels for plant tissue culture application.